2018
DOI: 10.1159/000495495
|View full text |Cite
|
Sign up to set email alerts
|

miR-650 Promotes the Metastasis and Epithelial–Mesenchymal Transition of Hepatocellular Carcinoma by Directly Inhibiting LATS2 Expression

Abstract: Background/Aims: Previous studies have confirmed that microRNAs are involved in the metastasis and epithelial–mesenchymal transition (EMT) of malignancies. In this study, we examined whether miR-650 promotes the migration, invasion, and EMT of hepatocellular carcinoma (HCC) cells by targeting the large tumor suppressor kinase 2 gene (LATS2). Methods: qRT-PCR was used to detect expression of miR-650 in HCC tissues and paired normal tissues. MTT and Transwell assay were used to observe the effect of miR-650 on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Increasing evidence indicates that a variety of miRNAs are aberrantly expressed in HCC. For example, miR-34a,9 miR-506,10 and miR-64511 are downregulated in HCC, whereas miR-197,12 miR-552,13 and miR-65014 are expressed at high levels in HCC. The dysregulated miRNAs exert their functions as oncogenes or tumor suppressors and play crucial roles in the initiation and progression of HCC 1517.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that a variety of miRNAs are aberrantly expressed in HCC. For example, miR-34a,9 miR-506,10 and miR-64511 are downregulated in HCC, whereas miR-197,12 miR-552,13 and miR-65014 are expressed at high levels in HCC. The dysregulated miRNAs exert their functions as oncogenes or tumor suppressors and play crucial roles in the initiation and progression of HCC 1517.…”
Section: Introductionmentioning
confidence: 99%
“…We selected 9 of the 26 dysregulated miRNAs for validation by RT-qPCR. These were selected on the basis of the most significantly deregulation (highest fold-regulation values) in combination with the literature (identified miRNA targets, cancer types, predictive function): over-expressed miRNAs were miR-650 [20,21,22], miR196a-5p [23,24,25,26], miR-142-5p [10,11] and miR-138-5p [27] and downregulated miRNAs were miR-135a-5p [28,29,30], miR-7-5p [31,32,33], miR-210-3p [34,35,36], miR-153-3p [37,38,39] and miR-203a-3p [11,12]] (Table 1, miRNAs in bold text). Two miRNAs of the final list, miR-142 and miR-135, were already analyzed based on the d3Tx mouse model [14].…”
Section: Resultsmentioning
confidence: 99%
“…Porcine follicular granulosa cells (pGCs) are important in follicles, and apoptosis of pGCs is the main cause of follicular atresia. In cells, miRNAs regulate a variety of important physiological and pathological processes, including cell proliferation (Han, Yin, & Zhang, ), differentiation (Wu et al, ), apoptosis (Yao, Pan, Du, Zhang, & Li, ), and hormone biosynthesis and secretion (Song et al, ). Previous studies have indicated that miR‐222 is an important regulatory factor for cancer development (Galardi et al, ; Gong et al, ; Gu et al, ; Guo et al, ; Huang, Ouyang, Wei, & Yu, ; Iida et al, ; le Sage et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%